Codzienne operacje arytmetyczne a problem kosztów podwójnego zadania: raport z eksperymentu behawioralnego kontrolowanego elektroencefalografem - Przybyła, Tomasz; Klichowski, Michał (Studia Edukacyjne, 2018)
Very recent studies show that a cognitive-motor interference can expose people not only to a motor danger but also weaken their cognitive capabilities. This effect is called the dual-task cost. One of the most popular examples of it nowadays is the smartphone use while walking, which is well examined. Yet, there are no studies that would analyse to what extent the other high-popular dual-task situation – shopping at the supermarket, weakens cognitive processes. To shed some light on this issue, we investigated a behavioral experiment on everyday mental calculations. Methods: Twenty mathematical-ly-educated adults took part in this study. We used stimuli in the form of shop labels. The participant’s task was to add two prices or state the price after a discount. They carried out the tasks by turns, either by standing (single-task) or walking with a shopping basket (dual-task). EEG controlled level of their attention. Results: We found that a cognitive-motor interference do not affected the everyday mental calculations. But, such familiar mental arithmetic as calculating prices after discounts was frighteningly difficultfor the participants. Conclusions: While our findingdoes not confirmthe occurrence of dual-task costs in everyday mental calculations, it has profound consequences for a mathematical education, which effects turn out to be useless in real life.